Trio Goo Katekis: Berguru Pada Yesus Sang Katekis Sejati - Marius Goo (JURNAL PASTORAL KATEKETIK, 2024)
Jesus the Catechist is dissected from a biblical, not Christological, perspective. The trio of Goo Catechists participated in Jesus the Catechist. They either preached about Jesus or followed Jesus for more than 50 years, even to old age and death. They have a very intimate closeness and attachment to Jesus, to the point that their whole lives are dedicated to Christ and His Church. They proclaim Jesus with faith in the context of the local culture, the Mee culture.